The Effects of Income, Wealth, and Capital Gains Taxation on Risk-Taking - Stiglitz, J. E. (Quarterly Journal of Economics, 1969)
I. Introduction, 263. — II. The basic model and some behavioral hypotheses, 264. — III. Wealth tax, 269. — IV. Income taxation, 270. — V. Special treatment of capital gains, 274. — VI. No loss offset, 275. — VII. Welfare implications, 279.